The Adverse Effect of the COVID-19 Labor Market Shock on Immigrant Employment - George J. Borjas; Hugh Cassidy (Institute of Labor Economics (IZA), 2020)
Employment rates in the United States fell dramatically between February 2020 and April 2020 as the initial repercussions of the COVID-19 pandemic reverberated through the labor market. This paper uses data from the CPS Basic Monthly Files to document that the employment decline was particularly severe for immigrants. Historically, immigrant men were more likely to be employed than native men. The COVID-related labor market disruptions eliminated the immigrant employment advantage. By April 2020, immigrant men had lower employment rates than native men. The reversal occurred both because the rate of job loss for at-work immigrant men rose relative to that of natives, and because the rate at which out-of-work immigrants could find jobs fell relative to the native job-finding rate. A small part of the relative increase in the immigrant rate of job loss arises because immigrants were less likely to work in jobs that could be performed remotely and suffered disparate employment consequences as the lockdown permitted workers with more "remotable" skills to continue their work from home.
Keywords: J21; J61; 330; immigration; labor supply; COVID-19